Optimalisasi Status Gizi Balita melalui Inovasi Pangan Lokal di Posyandu Mangga sebagai Upaya Pencegahan Stunting - Al Mar’atul Latifah; Ifa Maulida; Ika Rohmah Setiowati Ningsih; Magnolia Nerelina Puspa; Reza Hilmy Luayyin (Yayasan Inspirasi El Burhani, 2026)
Introduction: Stunting remains one of the major nutritional problems in Indonesia, affecting children’s health and development in the long term. Community-based interventions utilizing local food resources are essential to address this issue. Objective: This Community Service Program (KKN) aimed to improve the nutritional status of toddlers through active community participation in the Posyandu Mangga, Triwung Kidul Village.Method: The program was implemented through posyandu assistance, nutrition education for parents, and the innovation of providing local food products such as papaya and corn pudding as nutritious supplementary foods. Result: The findings showed an increase in body weight among most toddlers, indicating an improvement in nutritional status. In addition, the program enhanced parents’ awareness of the importance of balanced nutrition and proper parenting. Conclusion: This KKN program demonstrates that the utilization of local food and the synergy between students, posyandu cadres, and the community can serve as an effective strategy for stunting prevention and contribute to sustainable health for future generations.